Expression of preadipocyte genes in apical papilla cells after treatment with crude water extract of Cuscuta japonica Choisy - Kantawong, Fahsai; Wongsit, Peeraya; Yang, Jianghua; Wanachantararak, Penpitcha; Nan, Jiang; Wu, Jianming (Journal of Associated Medical Sciences, 2021)
Background: Cuscuta japonica Choisy (Japanese dodder) is a well-known traditional Chinese herbal medicine that has been used since ancient times as longevity and rejuvenation remedies, especially, in the southern part of China. The effects of this herb are widely known and can be applied for the treatment of a number of physiological diseases, but there is a lack of evidence describing its effects. Objectives: This study focused on observing global change of gene expression after long-term treatment with high dose of crude water extract from Cuscuta japonica Choisy. Materials and methods: In this research, dodder seeds were blended and boiled in distilled water before freeze drying to preserve as dried powder. UHPLC-QTOF-MS/MS was employed to test for important compounds in the extract of Cuscuta japonica Choisy. The extract at the concentration of 250 µg/mL was tested with apical papilla cells for 10 days to screen for change of gene expression by RNA sequencing before confirmation with real-time PCR. Results: UHPLC-QTOF-MS/MS result found glycosides, phenolic acids and flavonoids as the main components in dodder seed water extract. Results from next-generation sequencing showed that dodder seed water extract significantly altered expression of 19 genes in apical papilla cells treated with the extract for 10 days (11 genes were increased while 8 genes were decreased). RT-PCR result of CD36 and SCARA5 genes showed correlated results with RNA sequencing. Conclusion: The active compounds found in dodder seed water extract were phenolic acid, flavonoids, polysaccharide, lignan and volatile oil. The RNA sequencing studied in apical papilla cells showed that dodder seed water extract affected only a few genes that played roles in metabolism which correlated to the properties of this herb that was described as supplementary in metabolic diseases.